PARADISE LOST AND THE NARRATION OF NATION IN SALMAN RUSHDIE’S MIDNIGHT’S CHILDREN - Olalquiaga, Mayra Helena Alves (Em Tese, 2009)
This article proposes a study of the appropriations of John Milton’s Paradise lostin Salman Rushdie’s Midnight’s children. Adapting Milton’s proposition of the “paradise within”, Rushdie explores new ways of viewing imperial national selfrepresentation and how post-colonial writing can relate to its constituting texts.